2021
DOI: 10.3390/polym13172995
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of the Cell Metabolic Activity, Cytotoxicity, Cell Attachment, and Inflammatory Reaction of Human Oral Fibroblasts on Polyetheretherketone (PEEK) Implant–Abutment

Abstract: The purpose of this research is to compare the cytotoxicity of polyetheretherketone (PEEK) and polyetherketoneketone (PEKK) with conventional dental implant–abutment materials, namely titanium alloy (Ti-6Al-4V) and yttria-stabilized tetragonal zirconia polycrystal (Y-TZP), to evaluate the cell metabolic activity, cytotoxicity, and inflammation potential of human oral fibroblasts (HOF) on these materials. Disk-shaped specimens were designed and prepared via a dental computer-aided manufacturing technology syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Besides its unique combination of chemical and physical properties, one of the most important advantages of PEEK (polyether ether ketone) is represented by its potential to show good biocompatibility towards oral tissues [ 80 , 87 , 91 ]. Recently, the study presented by Peng et al confirmed that, under the same culture conditions, PEEK (polyether ether ketone) incubated human oral fibroblasts showed cell adhesion effectiveness, metabolic activity, and pro-inflammatory responses similar to titanium alloy incubated fibroblasts [ 92 ]. Cell adhesion represents a vital molecular process for fibroblasts in order to survive on a material surface; only after the completion of this molecular event can other important cellular phenomena—such as cell proliferation, differentiation, diffusion and migration—take place [ 92 , 93 , 94 , 95 ].…”
Section: Interim Prosthetic Materials Used For Obtaining Implant-supp...mentioning
confidence: 99%
See 4 more Smart Citations
“…Besides its unique combination of chemical and physical properties, one of the most important advantages of PEEK (polyether ether ketone) is represented by its potential to show good biocompatibility towards oral tissues [ 80 , 87 , 91 ]. Recently, the study presented by Peng et al confirmed that, under the same culture conditions, PEEK (polyether ether ketone) incubated human oral fibroblasts showed cell adhesion effectiveness, metabolic activity, and pro-inflammatory responses similar to titanium alloy incubated fibroblasts [ 92 ]. Cell adhesion represents a vital molecular process for fibroblasts in order to survive on a material surface; only after the completion of this molecular event can other important cellular phenomena—such as cell proliferation, differentiation, diffusion and migration—take place [ 92 , 93 , 94 , 95 ].…”
Section: Interim Prosthetic Materials Used For Obtaining Implant-supp...mentioning
confidence: 99%
“…Recently, the study presented by Peng et al confirmed that, under the same culture conditions, PEEK (polyether ether ketone) incubated human oral fibroblasts showed cell adhesion effectiveness, metabolic activity, and pro-inflammatory responses similar to titanium alloy incubated fibroblasts [ 92 ]. Cell adhesion represents a vital molecular process for fibroblasts in order to survive on a material surface; only after the completion of this molecular event can other important cellular phenomena—such as cell proliferation, differentiation, diffusion and migration—take place [ 92 , 93 , 94 , 95 ]. All these cellular phenomena are strongly correlated with collagen secretion, tissue regeneration, and wound healing.…”
Section: Interim Prosthetic Materials Used For Obtaining Implant-supp...mentioning
confidence: 99%
See 3 more Smart Citations